Pembuatan Video Promosi Produk Menggunakan CapCut di Instagram untuk Meningkatkan Brand Awareness pada Warung Bakso Boss Lumajang - Areta Annora Safir; Umi Khabibah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Advancements in information technology have made social media a vital tool for communication and promotion, with Instagram widely used to reach broad audiences and boost consumer engagement. This study was motivated by suboptimal promotion at Warung Bakso Boss Lumajang, where existing content lacked visual appeal and clear messaging, resulting in low brand awareness. This study aimed to develop a product video as a promotional medium using the CapCut application, published on Instagram, to increase brand awareness for Warung Bakso Boss Lumajang. The Action Research method was employed, comprising planning, action, observation, and reflection. The units of analysis included one owner, two multimedia experts, two computer experts, and ten potential customers, assessed using the EPIC Model (empathy, persuasion, impact, and communication dimensions). Results showed an EPIC rate of 4.37, categorized as very effective, and a Brand Awareness score of 88%, indicating an excellent level of awareness. These findings suggest that the promotional video is effective in boosting brand awareness. It is concluded that promotional videos created with CapCut and published on Instagram can increase brand awareness for Warung Bakso Boss Lumajang.